2021
DOI: 10.3390/w13172398
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of the Local Community Perspective on Ecotourism Development in Lombok, Indonesia

Abstract: This study examined stakeholders’ perception related to the Korea–Indonesia international ecotourism official development assistance project in Tunak, Lombok, Indonesia. In-depth interviews were conducted with 18 local community members, government officers, and project executors in 2014 and 2020. Six themes arose from the respondents’ perceptions: nature appreciation, enhancement of sociocultural development, prospect of stakeholder involvement, boosting environmental conditions, present economic contribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…Assistance is carried out collaboratively with stakeholders such as the Talaga Paca village government, the North Halmahera Regency and the Social Forestry and Environmental Partnership Agency of Maluku Papua Region. Collaboration makes it possible to carry out various activities more effectively and efficiently due to the sharing of resources between the parties [8]. This study conducted questionnaires to 30 people from the Talaga Paca village who were randomly selected to find out the community's response to the social forestry and ecotourism programs in relation with the community empowerment and conservation using the Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Assistance is carried out collaboratively with stakeholders such as the Talaga Paca village government, the North Halmahera Regency and the Social Forestry and Environmental Partnership Agency of Maluku Papua Region. Collaboration makes it possible to carry out various activities more effectively and efficiently due to the sharing of resources between the parties [8]. This study conducted questionnaires to 30 people from the Talaga Paca village who were randomly selected to find out the community's response to the social forestry and ecotourism programs in relation with the community empowerment and conservation using the Likert scale.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, local authorities are required to demonstrate civic competence to develop the requisite engagement with community leaders. Nur Syamsi and Lee (2021) found that the collaboration between formal and informal leaders creates a powerful team. This working group is known as the "Local Committee," comprising various participants, i.e., community leaders, a sub-district counselor, a secretary who represents the local agencies, and leaders of other communities.…”
Section: Alliance With Local Authorities and Relevant Agenciesmentioning
confidence: 99%
“…Nur Syamsi and Lee's (2021) study on ecotourism development in Lombok, Indonesia revealed that women employed in the tourism industry are at a disadvantage. Nevertheless, they reported that tourism businesses have positively impacted the roles and economic condition of the local community, such that some concerted efforts and capacity-building programs have now granted more opportunities to women to improve their participation in the industry.…”
Section: Women Empowermentmentioning
confidence: 99%
“…Most of the research results show that people's perceptions can lead to different attitudes towards ecotourism (Chen et al, 2020;Harianto et al, 2020;Saikim., 2020;Siahaya et al, 2021;Tebaiy, 2021;Syamsi and Lee., 2021;Stanciu et al, 2022;Gultekin, 2022). In this study, the perceptions that are the focus of attention are public perceptions related to ecotourism management activities, availability of ecotourism facilities and infrastructure, access to and information on ecotourism, and the impact of ecotourism.…”
Section: Introductionmentioning
confidence: 99%